Samesame but different? Consumer Sales Contracts and Burden of Proof Regarding the Damage in EU Member States - Schewe, Christoph (Journal of the University of Latvia. Law, 2017)
The EU internal market brings companies the possibility to offer goods and services on a market of 28 member states without facing considerable additional costs. Correspondingly, consumers benefit from enhanced competition, which leads to a broader variety of goods, higher quality and lower prices. Against this backdrop, it was also necessary to adjust or harmonize the legal regimes regarding the obligations of producers/companies and the rights of consumers, to avoid different standards in different places in the internal market. One of the instruments aiming at the harmonization of consumer rights was the Consumer Rights Directive 1999/44/EC. However, directives frequently bring along the question, whether the application in 28 member states succeeds to achieve the same standards regarding the aims and legal content of the directive. In 2015, this aspect became subject of a dispute in the Netherlands, making it necessary to request clarification by the Court of Justice of the European Union (CJEU) regarding the reach of Art. 5(3) of Directive 1999/44/EC and thus implicitly comment on the application of this provision in the EU member states. The decision regards a provision shifting the burden of proof in favour of the consumer. The article presents this CJEU-decision and, with a view to a relevant recent decision of the German Bundesgerichtshof (BGH) compares the current legal situations in Germany and Latvia.